Election news in six European countries: what is covered and how? – Study for research project - Salgado, Susana (2017)
This research project analyses the coverage of national elections that happened around the same time (between September 2015 and February 2016), in six European countries (Greece, Portugal, Poland, Croatia, Spain, and Ireland) where different issues were at stake. Questions, such as the following, guide the overall analysis: Which issues are most covered by the news media and how? In what ways is news election coverage similar and different in these countries? Are there distinctive patterns of election news coverage in these countries?